KUALITAS LINGKUNGAN KERJA DAN TEKANAN PSIKOLOGIS SEBAGAI DETERMINAN EFISIENSI PELAYANAN PUBLIK: STUDI PADA DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN GOWA - Bahar, Tri Ansari (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2024)
This study aims to determine the influence of Communication and Teamwork on Employee Performance at Almadera Hotel Makassar. This research used a quantitative approach with a sample about of 61 respondents. Data collection techniques were carried out through observation, documentation, and the distribution of questionnaires. Data analysis was conducted using multiple linear regression tests and hypothesis testing through the t-test. Based on the Communication variable, the calculated t-value is 4.466, which is greater than the t- table value of 2.002. In addition, the significance value (Sig.) of 0.000 is also smaller than 0.05. The Teamwork variable has a calculated t- value of 2.216, which is also greater than the t-table value of 2.002. Moreover, the significance value of 0.031 is less than 0.05. Thus, it can be concluded that Communication and Teamwork have a positive and significant effect on Employee Performance. This study shows that overall, the Communication and Teamwork variables jointly contribute strongly to Employee Performance at Almadera Hotel Makassar.Keywords : Communication, Teamwork, Employee Performance.